The outcomes of stand alone polyetheretherketone cages in anterior cervical discectomy and fusion - Abdulaziz F. Ahmed (14150082) (2022)
The procedure of anterior cervical discectomy and fusion is considered as the treatment of choice in degenerative disc disease, which material provides the best clinical and radiological fusion and other outcomes remains heavily debated. Materials that augment the process of fusion consist of bone grafting, titanium, polyetheretherketone (PEEK), or carbon cages. The application of PEEK cages has been recommended as it is radiolucent, and it has a modulus of elasticity that is similar to cortical bone. PEEK cages can be either filled with various materials or unfilled cages. Filled PEEK cages can include bone autografts, bone allografts, demineralized bone matrix, and other materials that facilitate fusion. This narrative review highlights that standalone filled PEEK cages were likely to have better radiological outcomes and satisfactory clinical outcomes for myelopathy when compared with standalone unfilled PEEK cages. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-020-04760-1